A Defeating Objection to Dynamic Block Theories of Time. (28th June 2016) - Lee, Barry
Abstract : McTaggart's argument against the reality of the A series (or some variation on that argument) poses a serious problem for the moving‐now block theory of time (MNBT). A defender of MNBT can respond along lines suggested by Broad: by denying that we should understand ' e was present' as saying that e is present at some past moment t . There is, however, a serious—plausibly defeating—objection to this type of response: it implicitly denies a non‐negotiable platitude about time. As a result, MNBT is not tenable. Growing block theories are also defeated by a similar objection.